The Effect of Financial Literacy, Financial Attitude and Personality on Financial Management Behavior: Pengaruh Literasi Keuangan, Sikap Keuangan dan Kepribadian Terhadap Perilaku Manajemen Keuangan - Listiyani, Rifdianti; Prapanca, Detak (Indonesian Journal of Innovation Studies, 2022)
This study aims to determine the effect of financial literacy, financial attitudes and personality on financial management behavior (study at Lazismu Umsida). This research is a type of quantitative research with hypothesis testing. The samples used in this study were 40 Lazismu Umsida volunteers. The analytical tool used in this study is multiple linear regression analysis using SPSS Version 22 for windows. The primary data in this study were obtained from a questionnaire whose measurement was using a Likert scale which was tested for validity and reliability. The results of this study prove that Financial Literacy has an effect on Financial Management Behavior, Financial Attitude has an effect on Financial Management Behavior, Personality has a negative and insignificant effect on Financial Management Behavior. In addition, Financial Literacy, Financial Attitude and Personality have a simultaneous effect on Financial Management Behavior.